Model discrimination in time-course kinetics : the glyoxalase pathway in S. cerevisiae - Lages, Nuno Filipe Gonçalves das, 1983- (2010)
Tese de doutoramento, Bioquímica (Bioquímica Teórica), Universidade de Lisboa, Faculdade de Ciências, 2010.